Can agricultural trade improve total factor productivity? Empirical evidence from G20 countries - Xu, Jialong; Wang, Yue; Zhao, Xing; Etuah, Seth; Liu, Zhen; Zhu, Hui (Frontiers in Sustainable Food Systems, 2023)
Improving agricultural total factor productivity is essential to achieving the high-quality and sustainable development of agriculture. As major global agricultural producers, the G20 countries play an important role in agricultural product trade and development. As such, it is well-positioned to play a positive role in improving agricultural total factor productivity. This paper uses the DEA-Malmquist index method to measure agricultural total factor productivity (TFP) in G20 countries from 2010 to 2019, and analyzes the impact of agricultural trade on TFP using the two-way fixed effects model. It finds that (1) the main source of agricultural TFP growth in G20 countries is technical progress, while the effect of technical efficiency on agricultural TFP is not obvious. (2) Agricultural trade can significantly improve agricultural TFP growth in G20 countries, and the effect is more obvious in developed countries. From the perspective of trade flow, the positive effect of export trade on agricultural TFP is stronger. (3) The institutional environment strengthens the improvement effect of agricultural trade on agricultural TFP. Thus, this study not only provides valuable insight into the relationship between agricultural trade and agricultural productivity, but also offers a strong argument in favor of the formulation of relevant policies to improve agricultural productivity and promote a more sustainable agricultural sector.